1976
DOI: 10.1007/bf00587288
|View full text |Cite
|
Sign up to set email alerts
|

The effects of different patterns of muscle activity on capillary density, mechanical properties and structure of slow and fast rabbit muscles

Abstract: When rabbit fast muscles were chronically stimulated at a frequency naturally occurring in nerves to slow muscles (10 Hz), there was a transformation towards a slow muscle type such as an increase of capillary density, increased activity of the oxidative enzyme, succinic dehydrogenase, and a decrease of muscle fibre diameters. After 28 days the intensity and distribution of SDH and the capillary density were similar to those of soleus. The increases in capillary density preceded the changes in activity of SDH;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
121
0
3

Year Published

1990
1990
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 251 publications
(137 citation statements)
references
References 23 publications
13
121
0
3
Order By: Relevance
“…However, using the same stimulation pattern Hudlick a & Tyler (1984) found an increased capillary supply after 14 days. Increases in capillary supply preceding the changes in oxidative enzymes were described previously (Pette et al 1973;Brown et al 1976), and were confirmed more recently (Skorjanc et al 1998) using different stimulation regimes than those used in the present study. It is normally assumed that increased activity of oxidative enzymes in muscles of endurance-trained animals is a sign of hypoxia which triggers capillary growth, possibly via vascular endothelial growth factor (VEGF; Breen et al 1996).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…However, using the same stimulation pattern Hudlick a & Tyler (1984) found an increased capillary supply after 14 days. Increases in capillary supply preceding the changes in oxidative enzymes were described previously (Pette et al 1973;Brown et al 1976), and were confirmed more recently (Skorjanc et al 1998) using different stimulation regimes than those used in the present study. It is normally assumed that increased activity of oxidative enzymes in muscles of endurance-trained animals is a sign of hypoxia which triggers capillary growth, possibly via vascular endothelial growth factor (VEGF; Breen et al 1996).…”
Section: Discussionsupporting
confidence: 88%
“…Physiol. 85.5 Although it is not possible to compare directly results from different species and stimulation regimes, Brown et al (1976) also reported the absence of capillary growth in rabbit muscles using 40 Hz for 4 days, but with a different pattern of stimulation (3 ² 5 s bouts min¢ for 8 h per day) and supramaximal voltage (which activates all muscle fibres). However, using the same stimulation pattern Hudlick a & Tyler (1984) found an increased capillary supply after 14 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the target organ is skeletal muscles, the method is called functional neuromuscular stimulation (FNS) (Peckham, 1981). FNS has been found to increase the capillary density in muscles (Brown et al, 1976) and to increase the skin blood flow (Hellsing, 1986). It also improves the fatigue resistance by increasing the oxidative metabolism in the stimulated muscles (Riley et ai., 1973).…”
mentioning
confidence: 99%
“…The origin of the transition from type I fibers to type II in soleus muscle of SHR still remains little known; however, studies show it is related to capillary rarefaction followed by alterations in the metabolic properties 11,28 . Studies show that, when there is a transition between the types of fibers of the skeletal muscle, the different morphological properties of the muscular fiber are changed in the following manner: the capillary density and the activities of the enzymes of the energetic metabolism are early altered during the transition and precede the change in the activity of the myofibrillar ATPase and the contractile characteristics of the muscle 8,29 . In mammals, the fibers of the skeletal muscle are usually classified in type I and type II fiber according to the different activities of the myosin ATPase after the pre-incubation in different pHs, and the type II fibers can be subclassified in IIA, IIX/D and IIB.…”
Section: Discussionmentioning
confidence: 99%